2017
DOI: 10.1371/journal.pone.0188187
|View full text |Cite
|
Sign up to set email alerts
|

Health assessment of French university students and risk factors associated with mental health disorders

Abstract: ObjectiveThe first year of university is a particularly stressful period and can impact academic performance and students’ health. The aim of this study was to evaluate the health and lifestyle of undergraduates and assess risk factors associated with psychiatric symptoms.Materials and methodsBetween September 2012 and June 2013, we included all undergraduate students who underwent compulsory a medical visit at the university medical service in Nice (France) during which they were screened for potential diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
3
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 42 publications
6
49
3
13
Order By: Relevance
“…In this study, students experiencing decreased grades than anticipated had higher odds of mental distress. This could imply that, university students are likely to experience depression, anxiety, frustration and troubles sleeping among other mental health issues due to stress associated with their academic lives [14,23,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, students experiencing decreased grades than anticipated had higher odds of mental distress. This could imply that, university students are likely to experience depression, anxiety, frustration and troubles sleeping among other mental health issues due to stress associated with their academic lives [14,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…University students with higher proportion of mental distress are likely to experience negative consequences such as significant impaired cognitive functioning, learning disabilities, poor academic performance, substance abuse (e.g. cigarette/tobacco smoking, alcohol use and khat chewing) which are associated with risk behaviors [8,14], higher risk of depression as well as anxiety disorders [8]. This indicates that, mental distress increases the risk of other mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…The scores for each question sum to a total score between 10-50, which corresponds to the following categories of non-specific psychological distress; low (10-15), moderate (16)(17)(18)(19)(20)(21), high (22)(23)(24)(25)(26)(27)(28)(29), or very high (30-50) risk.…”
Section: Psychological Distressmentioning
confidence: 99%
“…Overall, these studies support that an unhealthy diet is associated with poorer mental health. For example, studies from Canada, France and the UK, found low fruit and vegetable intakes, higher intakes of added sugars, sweets and fast food, as well as irregular meal patterns were associated with higher odds of depression, anxiety and stress [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing changes in society and family structures were reflected in the results, including the fact that it became more common to live in larger cities and alone from 1999 to 2009. Both urbanization [30,31] and living alone [32] may pose mental health challenges, particularly for vulnerable individuals. There were more parental divorces in 2009 than in 1999.…”
Section: Discussionmentioning
confidence: 99%